(untitled) (The Research of Medical Science Review, 2024)
Background: Physical examination skills are critical for nurses, but many report they are underutilized due to heavy workloads, insufficient training, and the perception that these tasks are primarily the responsibility of doctors. Addressing these challenges is essential for improving patient care and optimizing nursing practice. Objective: The primary aim of this study was to assess the attitudes of staff nurses towards physical examination skills at People's Medical College Hospital, Nawabshah. Research Methodology: A cross-sectional study was conducted from July to September 2024. The sample comprised 82 staff nurses selected using non-probability convenience sampling. Data were analyzed using IBM SPSS version 23.Results: The study found that 77% of respondents acknowledged that physical examinations are crucial for fostering patient confidence, and 86.6% believed these skills enhance their self-worth and positively contribute to patient care. However, a significant number (73.2%) of nurses viewed diagnostic procedures as more beneficial than physical examinations. Additionally,70.7% of respondents identified increased workloads as a key barrier to conducting thorough physical examinations.Conclusion: The study concluded that nurses express a positive attitude toward the importance of physical examination for patient care. However, notable barriers, such as heavy workloads and the perception that physical examinations should be conducted by doctors, hinder their practice. Overcoming these challenges through improved training, interprofessional collaboration, and stronger support structures will help empower nurses and enhance patient care.